Analisis Kepuasan Pelanggan Pada UD. Usaha Kita dengan Metode TQM dan PDCA Menggunakan Uji Regresi Linear Berganda dengan Software SPSS - Selviana R. Dania; Dwi Sukma Donoriyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Usaha Kita is a business that operates in the field of chemical production. UD. Usaha Kita produces porcelain or cleaning fluid to remove stubborn dirt on porcelain and ceramic surfaces and can also eradicate disease-carrying germs. Customer satisfaction is the key to success in a business. Satisfied customers will become loyal customers so they will tend to make repeat purchases and become promoters of the product. These customers will ultimately increase UD's income. Our Business. The purpose of writing this research is to find out and review from a theoretical perspective various literature and analyze the quality of Porsche product services on customer quality. In analyzing this problem, the method that will be used is a multiple linear regression test to determine the level of customer satisfaction in selling porstex at UD. Usaha Kita. In this case, after implementing TQM and PDCA, most of it can be seen in the quality of workers and also in management.